2020
DOI: 10.3389/fnmol.2020.00138
|View full text |Cite
|
Sign up to set email alerts
|

Gut Metabolite TMAO Induces Synaptic Plasticity Deficits by Promoting Endoplasmic Reticulum Stress

Abstract: Dysbiosis of gut microbiota is strongly associated with metabolic diseases including diabetes mellitus, obesity, and cardiovascular disease. Recent studies indicate that Trimethylamine N-oxide (TMAO), a gut microbe-dependent metabolite is implicated in the development of age-related cognitive decline. However, the mechanisms of the impact of TMAO on neuronal function has not been elucidated. In the current study, we investigated the relationship between TMAO and deficits in synaptic plasticity in an Alzheimer’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 45 publications
(64 reference statements)
2
61
0
Order By: Relevance
“…pathways. Finally, several recent studies have reported that TMAO can directly increase the production of reactive oxygen species ( Govindarajulu et al, 2020 ; Wu et al, 2020 ; Chang et al, 2021 ). The excessive production of reactive oxygen species caused by oxidative stress plays an important role in the pathogenesis of DKD ( Jha et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…pathways. Finally, several recent studies have reported that TMAO can directly increase the production of reactive oxygen species ( Govindarajulu et al, 2020 ; Wu et al, 2020 ; Chang et al, 2021 ). The excessive production of reactive oxygen species caused by oxidative stress plays an important role in the pathogenesis of DKD ( Jha et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each train contains four pulses at 100 Hz, with an inter-burst interval of 200 ms. The recording was continued for 60 min post-TBS ( Bloemer et al., 2019 ; Govindarajulu et al., 2020 ). LTP was calculated as an average of fEPSP slopes from 50-60 min post induction.…”
Section: Methodsmentioning
confidence: 99%
“…However, it must be noted that carnitine is not a primary pre-curser of TMA, as discussed below. Aged animal models show higher TMA absorption into the portal vein and eventual TMAO accumulation compared to the young, indicating that changes at the host enterocytes also influences serum TMAO accumulation [ 92 , 93 , 94 ].…”
Section: Tmao Accumulation In Serummentioning
confidence: 99%
“…This elevated expression may be compensatory due to increased TMA substrate load but may also represent FMO3 expression regulation by TMAO [ 36 ]. Mice models of over-nutrition have elevated FMO3 expression [ 36 , 93 , 117 , 134 ]. Conversely, one hepatocyte cell culture study showed that free fatty acid treatment inhibited FMO1, 3, and 5 expression [ 135 ].…”
Section: Tmao Accumulation In Serummentioning
confidence: 99%
See 1 more Smart Citation